1997
DOI: 10.1007/s002469900178
|View full text |Cite
|
Sign up to set email alerts
|

Normal Ranges of Heart Rate Variability During Infancy and Childhood

Abstract: Heart rate variability is a noninvasive index of the neural activity of the heart. The present study examined heart rate variability indices in 210 infants and children aged 3 days to 14 years to obtain normal ranges for all age classes. Heart rate variability was measured by calculating mean RR interval over the length of the analysis, mean RR interval during quiet sleep, 5 time-domain (SDNN, SDNN-i, SDANN-i, r-MSSD, pNN50), and 4 frequency-domain (VLF, LF, HF, LF/HF ratio) indices. Our data show a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
126
1
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 34 publications
(44 reference statements)
25
126
1
8
Order By: Relevance
“…Age has sometimes been noted to be associated with these stress-sensitive physiological measures (Finley & Nugent, 1995;Kazuma, Otsuka, Wakamatsu, Shirase, & Matusoka, 2002;Lenard, Studinger, Mersich, Kocsis, & Kollai, 2004;Massin & von Bernuth, 1997;Silvetti, Drago, & Ragonese, 2001). As already noted, sex differences were obtained for measures of fearful temperament.…”
Section: Preliminary Analyses Of Physiological Measuresmentioning
confidence: 69%
See 1 more Smart Citation
“…Age has sometimes been noted to be associated with these stress-sensitive physiological measures (Finley & Nugent, 1995;Kazuma, Otsuka, Wakamatsu, Shirase, & Matusoka, 2002;Lenard, Studinger, Mersich, Kocsis, & Kollai, 2004;Massin & von Bernuth, 1997;Silvetti, Drago, & Ragonese, 2001). As already noted, sex differences were obtained for measures of fearful temperament.…”
Section: Preliminary Analyses Of Physiological Measuresmentioning
confidence: 69%
“…Children who showed greater parasympathetic withdrawal to the fear video showed larger heart rate increases, r(139) = . 60, p <.001; while there was no association between changes in PEP and heart rate, r(160) = −.10, ns.The measure of cortisol response (Cort AUC ) had a positive mean, although there was great variability in response, and a one-sample test of the area under the curve was only Age has sometimes been noted to be associated with these stress-sensitive physiological measures (Finley & Nugent, 1995;Kazuma, Otsuka, Wakamatsu, Shirase, & Matusoka, 2002;Lenard, Studinger, Mersich, Kocsis, & Kollai, 2004;Massin & von Bernuth, 1997;Silvetti, Drago, & Ragonese, 2001). As already noted, sex differences were obtained for measures of fearful temperament.…”
mentioning
confidence: 69%
“…Unique developmental changes and pediatric milestones preclude these adult findings from being extrapolated to children. Altogether, the state of knowledge regarding "normal" HRV values in children is rather haphazard [8,23,37,43]. The objectives of the present study were twofold.…”
Section: Introductionmentioning
confidence: 98%
“…Especially, heart rate variability (HRV) with frequencydomain analysis has emerged as a noninvasive method to assess cardiac autonomic activity quantitatively, and it seems to be highly reproducible under standardized conditions (Massin and von Bernuth 1997;Batten et al 2000). Also, it has been suggested that subjects with low HRV had an adverse cardiovascular risk profile and an elevated risk of incident CHD and death (Dekker et al 2000), and that cardiovascular autonomic function played an important role in increasing blood pressure levels associated with increased modulation of parasympathetic tone of the heart after puberty but not in preadolescents (Tanaka et al 2000).…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%